SUSTAINABLE TOURISM IN ISLAND DESTINATION : A STUDY AT SAMALONA ISLAND, INDONESIA - Agustin Aulia (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
This study aims to analyze the implementation of sustainable tourism principles in small island destinations, using Samalona Island in Makassar as a case study. The focus of the research is to understand the dynamics of environmentally friendly tourism management while simultaneously providing socio-economic benefits to the local community. This study uses a descriptive qualitative approach, with data collection techniques through interviews, field observations, and documentation. Thematic analysis was conducted to describe stakeholder involvement, forms of community participation, and the challenges and opportunities faced in developing sustainable tourism. The results indicate that Samalona Island has significant marine tourism potential, but is also vulnerable to marine ecosystem damage due to increasing tourist numbers and limited environmental carrying capacity. The government plays a role in providing basic policies and infrastructure, local communities contribute through community-based tourism management, businesses strengthen the tourism and culinary services sectors, academics support with research and mentoring, and the media plays a role in destination promotion. The level of collaboration among stakeholders has been quite good, although obstacles remain, such as limited funding, a lack of environmental awareness among some tourists, and weak coordination between parties. The main challenges identified include the threat of ecosystem degradation, potential conflicts of interest between stakeholders, and a lack of regulations regarding tourist visit capacity. However, significant opportunities also exist, such as strengthening the local economy through culinary and ecotourism businesses, increasing human resource capacity through training, and utilizing digital technology for environmental promotion and monitoring. Based on these findings, the study recommends strategies such as strengthening cross-sector collaboration using the pentahelix model, increasing tourist awareness of environmental sustainability, and implementing visitor capacity regulations. If these strategies are consistently implemented, Samalona Island has the potential to become a model for developing sustainable small island tourism destinations in Indonesia, capable of preserving the environment while improving the welfare of local communities.